2021
DOI: 10.3390/ijms22031304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Lipid Accumulation and Metabolism of Oleaginous Chlorococcum sphacosum GD from Soil under Salt Stress

Abstract: The oleaginous microalgae species Chlorococcum sphacosum GD is a promising feedstock for biodiesel production from soil. However, its metabolic mechanism of lipid production remains unclear. In this study, the lipid accumulation and metabolism mechanisms of Chlorococcum sphacosum GD were analyzed under salt stress based on transcriptome sequencing. The biomass and lipid content of the alga strain were determined under different NaCl concentrations, and total RNA from fresh cells were isolated and sequenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In recent years, the development of transcriptomics technology has promoted the study of the gene functions of various biological processes in microalgae. To date, the molecular mechanisms and relevant genes of microalgae responding to heavy metals, salt, pollutants, and some other stress conditions have been reported (Su et al, 2021; Tripathi & Poluri, 2021; Zhao, Tang, Lv, et al, 2020). For high light stress, Nymark et al (2009) combined global transcriptional profiling and metabolite profiling analysis and observed that Phaeodactylum tricornutum went through three phases of photoacclimation after transferring from 35 μmol photons · m −2 · s −1 to 500 μmol photons · m −2 · s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of transcriptomics technology has promoted the study of the gene functions of various biological processes in microalgae. To date, the molecular mechanisms and relevant genes of microalgae responding to heavy metals, salt, pollutants, and some other stress conditions have been reported (Su et al, 2021; Tripathi & Poluri, 2021; Zhao, Tang, Lv, et al, 2020). For high light stress, Nymark et al (2009) combined global transcriptional profiling and metabolite profiling analysis and observed that Phaeodactylum tricornutum went through three phases of photoacclimation after transferring from 35 μmol photons · m −2 · s −1 to 500 μmol photons · m −2 · s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the types of organic acids (12) and lipids (six) increased by more than 2-folds when GXDK6 was stressed by 10% NaCl. Therefore, the accumulation of organic acids and lipids is likely beneficial to GXDK6 to increase its resistance to salt stress (30). Among the metabolites, glycerol was found as the consistent product when the NaCl concentration was increased from 0% to 10%; the corresponding glycerol decreased from 14.99% to 8.88%, with a decrease by 40.76%, demonstrating that glycerol is one of the important substances in response to salt tolerance (31).…”
Section: Proteomics Analysis Of Gxdk6 Under Nacl Stressmentioning
confidence: 94%
“…The main enzyme involved in the precursor formation and lipid synthesis are ACCase, ATP citrate lyase (ACL), glycerol-3-phosphate (GPAT), lysophosphatidic acid acyltransferase (LPAAT), phospholipid: diacylglycerols acyltransferase (PDAT), and acyl-Co-A: diacylglycerols acyltransferase (DGAT) [52][53][54]. The expression of these gene-encoding enzymes determines lipid content, and the regulation of these genes affects lipid content [55,56].…”
Section: Overexpression Of Gene/enzymes Involved In the Lipid Biosynt...mentioning
confidence: 99%